STUDENTS’ PERCEPTION ON GAME FOR VOCABULARY MASTERY - Kiling, Sarah; Tuerah, Ignatius J.; Posumah, Jennie (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The objective of this study was to determine students’ perspectives regarding the utilization of games to enhance vocabulary mastery. The researcher employed a questionnare as the primary tool for data collection. A descriptive survey method was utilized to analyze the gathered data. This approach involved directly obtaining information from individuals. The research targeted students from SMA Katolik Rosa de Lima Tondano, with sample size of 30 participants. The research findings revealed that the sampled students had s significant level of experience in enhancing their vocabulary through game-based learning, and the majority of their responses reflected a positive perception. As a result, it could be concluded that employing games for vocabulary development was effective for students at SMA Katolik Rosa de Lima Tondano. English teachers recommended to consistently enhance the technology used and teaching methods. Enabling the implementation of improvements in the classroom and facilitating the positive impact of game-based vocabulary learning